Strategic Leadership of School Administrators Affecting Teachers’ Academic Performance Under the Secondary Educational Service Area Office Bangkok 2 - Prasansook, Sita (Academic MCU Buriram Journal, 2024)
The purpose of this research were: 1) study the strategic leadership level of educational institution administrators. Under the jurisdiction of the Bangkok Secondary Educational Service Area Office, Area 2 2) study the academic performance level of teachers Under the jurisdiction of the Bangkok Secondary Educational Service Area Office, Areas 2 and 3) studied the strategic leadership of school administrators that affects teachers’ academic performance. Under the jurisdiction of the Bangkok Secondary Educational Service Area Office, Area 2. The sample group is 52 educational institutions, with the informants consisting of 1) 13 administrators and 2) 348 teachers, totaling 361 people. Tools used the research is a questionnaire. It has a confidence value of 0.9. Statistics used in data analysis include percentage, mean, and standard deviation. Pearson’s correlation coefficient and stepwise multiple regression analysis. The research results found that: 1. Strategic leadership of school administrators Secondary school Under the jurisdiction of the Bangkok Secondary Educational Service Area Office, Area 2, overall, it is at a high level 2. Academic performance of secondary school teachers. Under the jurisdiction of the Bangkok Secondary Educational Service Area Office 2, the overall level is at a high level and 3. the relationship between the strategic leadership of school administrators and the academic performance of secondary school teachers. Under the jurisdiction of the Bangkok Secondary Educational Service Area Office 2, it was found that revolutionary thinking and the implementation of strategies can jointly predict and has a predictive power value of 60.60% with statistical significance at the .01 level. A prediction equation can be created in the form of raw scores and standard scores, which are.